Evaluation of Functional Outcome of Single Dose Intralesional Autologous Blood Vs Corticosteroid Injection in Chronic Plantar Fascitis - Kandel, Sandip; Dhital, Aditi; Khatik, Chandra (Journal of Nepalgunj Medical College, 2024)
Introduction: Plantar fascitis is one of the main underlying causes of acute and chronic heel pain. Diagnosis is mainly based on clinical symptoms and most of the time diagnostic imaging is not required routinely. Corticosteroid injection and autologous blood injection has been a possible means of treatment. Injection of autologous blood can help stimulate a healing response in chronic tendon disorders. Aims: To compare the functional outcome of single dose intra-lesional injection of autologous blood and corticosteroid in chronic plantar fascitis. Methods: This study was done in Nepalgunj medical college and teaching hospital during the period of March 2023 to August 2023 in the department of orthopedics. Sixty patients were enrolled in the study with 30 patients in each group. The patients were selected according to our inclusion and exclusion criteria and diagnosis made on clinical examination alone. The pain status was noted on the visual analog scale and the activity level noted based on the Nirschl stage. The final outcome was based on our scoring system based on the pain status and the activity level at two, four- and twelve-weeks’ duration and graded into four categories as excellent, good, and acceptable and poor. Results: We found that in chronic plantar fascitis, local intralesional steroid injection gives better pain relief and faster return to activities of daily living compared to autologous blood injections. In our study we found that 17.85% had excellent outcome, 35.72% had good outcome and 12% had acceptable outcome in steroid group, whereas in autologous blood group 7.40% had excellent, 22.22% had good and 70.37% had acceptable outcome respectively. Conclusion: Intralesional steroid injection in chronic plantar fascitis have shown to achieve better functional outcome than autologous blood injection.